Online Gaming and Students’ Academic Performance in Nepal: Towards Sustainable Development of Digital Educational Games for Students - Gautam, Ramesh (Academia Journal of Humanities & Social Sciences, 2026)
This paper aims to explore a connection between the online game addiction and academic achievement among the secondary school level students in Nepal. As the digital gaming has expanded, there are some questions of its possible effects on the students’ learning due to their behavioral outcomes. A quantitative and descriptive-correlational design was utilized in this study whereby 120 secondary students were sampled from the public and private schools in Pokhara Metropolitan City for data collection. Statistical tests, such as descriptive statistics, the Pearson correlation and multiple regression were performed in SPSS. The findings showed a negative significant relationship between the online gaming addiction and academic achievement of students whereby higher the gaming addiction scores, the lower the grade point average (GPA) and the lower the attendance of classes among students. These results demonstrate the negative academic consequences of gaming addiction and underline the significance of moderate digital activity and parental controls and school-based interventions. The empirical data presented in the study is a contribution to the expanding body of literature on the topic of behavioral addiction, offering few solutions to encourage the responsible digital behavior among teenagers. Finally, the findings highlight the urgent need for awareness, digital literacy, and counseling programs promoting the balanced technology use in schools.